Therapeutic Effect and Mechanism of Si-Miao-Yong-An-Tang on Thromboangiitis Obliterans Based on the Urine Metabolomics Approach - Li, Hui-Yu; Sun, Hui; Zhang, Ai-Hua; He, Lu-Wen; Qiu, Shi; Xue, Jun-Ru; Wu, Fangfang; Wang, Xi-Jun (Frontiers in Pharmacology, 2022)
Si-Miao-Yong-An-Tang (SMYAT) is a classic prescription for the treatment of thromboangiitis obliterans (TAO) with definite curative effect. This experiment uses urine metabonomics to evaluate the therapeutic effect and mechanism of SMYAT on sodium laurate solution induced thromboangiitis obliterans model rats. To evaluate the therapeutic effect of SMYAT by histopathology, hemorheology and other indexes. The urine metabonomics method, principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) were used for clustering group and discriminant analysis to screen urine differential metabolic biomarkers, and to explore the mechanism of SMYAT in the treatment of TAO. SMYAT has significant antithrombotic and anti-inflammatory effects, according to the results of urine metabonomics analysis, SMYAT can regulate the disorder metabolic profile of TAO rats, and its return is close to the state of control group. Through metabolomics technology, a total of 38 urine biomarkers of TAO model were characterized. Among them, SMYAT treatment can regulate 23 core biomarkers, such as normetanephrine and 4-pyridoxic acid. It is found that the therapeutic effect of SMYAT is closely related to the tyrosine metabolism, vitamin B6 metabolism and cysteine and methionine metabolism. This study preliminarily explored the therapeutic mechanism of SMYAT, and provided scientific basis for the clinical application of SMYAT.